Advances in Marine Natural Product Characterisation and Separation Methodologies - Urban, Sylvia; Urban, Sylvia (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The search for bioactive marine natural products calls for the need of efficient chemical profiling strategies, together with the need to make advances in separation and characterization methodologies, in order to expedite their discovery. This Special Issue of Marine Drugs aims to highlight advances in extraction, isolation, purification and dereplication methodologies in the quest for bioactive marine natural products.
English
Keywords: Research & information: general; Chaceon quinquedens; cold water species; red deep-sea crab; insulin-like androgenic gland hormone (IAG); androgenic gland; bioguided-discovery; dereplication; cytotoxicity; antifungal; MS/HRMS; marine-derived; pimarane-type diterpenoids; ilicicolin H; trichothecene mycotoxins; roridin; verrucarin; high-speed countercurrent chromatography; preparative separation; stepwise elution; Eustigmatos cf. polyphem; violaxanthin; culture conditions; purification; antioxidant activity; Mosher; retroflexanone; phloroglucinol; HPLC-NMR; secondary alcohol; cephalimysins; Aspergillus fumigatus; marine microorganism; Mugil cephalus; spiro-heterocyclic gc(B-lactams; circular dichroism spectroscopy; hydroxypropyltrimethyl ammonium chloride chitosan; halogenated acetate; antifungal activity; electronegativity; microalgae; Haematococcus pluvialis; astaxanthin; lutein; fatty acids; supercritical fluid extraction; natural medicines; chondroitin sulfate production; cartilage Galeus melastomus by-products; sulfation patterns; process optimization; molecular weight glycosaminoglycans determination; bycatch waste management; electronic circular dichroism; absolute configuration; molecular conformation; electric transition dipole moment; exciton coupling; TDDFT calculations